Digital Development in Korea: Lessons for a Sustainable World, 2nd edition - Oh, Myung (Routledge, 2020)
Digital Development in Korea explores the central role of digital information and communication technology in South Korea. Analyzing the role of ICT in green growth and sustainability, this new edition also demonstrates how concerns over public safety and the Olympic Games are shaping next generation digital networks.